ANALISIS PERMINTAAN KEDELAI SEBAGAI BAHAN BAKU AGROINDUSTRI TAHU DI KABUPATEN GARUT - Muhamad Nu'man Adinasa; Fitri Awaliyah (Universitas Galuh Ciamis, 2021)
Soybean is a consumption material for the food processing industry, one of products is tofu and one of the most abundant and continuously produced throughout the year. The production of tofu in Garut Regency is also carried out by enterprises with different formulations even though the technicalities and raw materials are the same. The need for soybeans can be viewed from their use as raw material by industry, the number of enterprises and the amount of soybeans used in each production to the total amount of soybeans that must be available. The current problem is that the fulfillment of soybeans is carried out through imports by the government and a small part is met from domestic production, however, government policy continues to strive to increase food production including soybeans to reduce dependence on imported soybeans. Garut Regency is one of the second largest soybean producers in West Java. This study aims to determine the use, differences in the composition of soybeans for each craftsman in the processing, as well as the fluctuation in the amount of soybean needs used by the enterprises in Garut Regency for one year. The research used quantitative descriptive analysis method which presented the research data which were described descriptively according to the field results. This study concludes that the need for soybeans cannot be replaced by local soybeans due to limited supply of quantity and time, other than that local soybeans are used for mixtures because of their superiority in increasing the number of products, then the supply of soybeans should be seen based on a certain period, not on a total annual basis because of fluctuations in demand. due to community habits and national and religious holidays.